Behavioral and cognitive functioning in individuals with Cantú syndrome. Issue 8 (30th May 2021) - Roessler, Helen I.; van der Heuvel, Lieke M.; Shields, Kathleen; Guilliams, Kristin P.; Knoers, Nine V. A. M.; van Haaften, Gijs; Grange, Dorothy K.; van Haelst, Mieke M.
Abstract: Cantú syndrome (CS) is caused by pathogenic variants in ABCC9 and KCNJ8 encoding the regulatory and pore‐forming subunits of ATP‐sensitive potassium (KATP ) channels. CS is characterized by congenital hypertrichosis, distinctive facial features, peripheral edema, and cardiac and neurodevelopmental abnormalities. Behavioral and cognitive issues have been self‐reported by some CS individuals, but results of formal standardized investigations have not been published. To assess the cognitive profile, social functioning, and psychiatric symptoms in a large group of CS subjects systematically in a cross‐sectional manner, we invited 35 individuals (1–69 years) with confirmed ABCC9 variants and their relatives to complete various commonly applied standardized age‐related questionnaires, including the Kaufman brief intelligence test 2, the social responsiveness scale‐2, and the Achenbach system of empirically based assessment. The majority of CS individuals demonstrated average verbal and nonverbal intelligence compared to the general population. Fifteen percent of cases showed social functioning strongly associated with a clinical diagnosis of autism spectrum disorder. Both externalizing and internalizing problems were also present in this cohort. In particular, anxiety, anxiety or attention deficit hyperactivity disorder, and autism spectrum behaviors were predominantly observed in the younger subjects in the cohort (≥25%), but this percentage decreased markedly in adults.